RANCANG BANGUN PEMASARAN PRODUK BADAN USAHA MILIK DESA (BUMDES) MERTA SEDANA SELAT BERBASIS WEB MENUJU SMART VILLAGE - Tutde, I Ketut Darma Nugraha; I Kadek Juni Arta; I Nyoman Bagus Suweta Nugraha (Jurnal Manajemen dan Teknologi Informasi, 2024)
The use of information technology in village development, as seen in the Smart Village in Merta Sedana Selat Village, has brought significant changes in the economic and service sectors. However, BUMDes Merta Sedana Selat still faces obstacles due to the lack of technology application in product marketing management. Therefore, the development of a web-based product marketing information system is a solution to help increase BUMDes' business and expand the reach of product marketing. The system uses the Waterfall method for its development, with appropriate hardware and software to support efficiency in product marketing management.